2008
DOI: 10.1186/1471-2202-9-60
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony between orientation-selective neurons is modulated during adaptation-induced plasticity in cat visual cortex

Abstract: BackgroundVisual neurons respond essentially to luminance variations occurring within their receptive fields. In primary visual cortex, each neuron is a filter for stimulus features such as orientation, motion direction and velocity, with the appropriate combination of features eliciting maximal firing rate. Temporal correlation of spike trains was proposed as a potential code for linking the neuronal responses evoked by various features of a same object. In the present study, synchrony strength was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 79 publications
(97 reference statements)
5
12
0
Order By: Relevance
“…This seems to be in line with investigations reporting that V1 (layer II/III) neurons receive a diversity of oriented inputs from surrounding neurons, however, there is an enhanced connectivity between neurons that share orientation preference (Monier et al, 2003;Jia et al, 2010;Ko et al, 2011). Recently, we have shown that cell-assemblies develop heightened functional connections to a suitable orientation, and may wax and wane contingent upon the presented orientation (Ghisovan et al, 2008;Duret et al, 2006;Bharmauria et al, 2012;Bretzner et al, 2001). Then the results of the present investigation suggest that the formation of an encoding assembly of excited neurons may rest on two global processes: firstly, to an appropriate stimulus, there is a development of functional connections leading to construction of a functional connectome particular to that stimulus; secondly, these connections allow enhanced responses leading to relevant and salient neural activities that participate in signaling a specific target.…”
Section: Functional Consequencessupporting
confidence: 70%
See 2 more Smart Citations
“…This seems to be in line with investigations reporting that V1 (layer II/III) neurons receive a diversity of oriented inputs from surrounding neurons, however, there is an enhanced connectivity between neurons that share orientation preference (Monier et al, 2003;Jia et al, 2010;Ko et al, 2011). Recently, we have shown that cell-assemblies develop heightened functional connections to a suitable orientation, and may wax and wane contingent upon the presented orientation (Ghisovan et al, 2008;Duret et al, 2006;Bharmauria et al, 2012;Bretzner et al, 2001). Then the results of the present investigation suggest that the formation of an encoding assembly of excited neurons may rest on two global processes: firstly, to an appropriate stimulus, there is a development of functional connections leading to construction of a functional connectome particular to that stimulus; secondly, these connections allow enhanced responses leading to relevant and salient neural activities that participate in signaling a specific target.…”
Section: Functional Consequencessupporting
confidence: 70%
“…However, recently, authors (Ainsworth et al, 2012) have suggested a bias toward a precise temporal code (stimulus-driven-synchrony) that is a reflection of the anatomical architecture and synaptic biophysical properties of neurons (Ratté et al, 2013;Ainsworth et al, 2012). Synchronized neural activity implying specific functional connectivity has already been associated to the generation of coherent percepts (Fujisawa et al, 2008;Barthó et al, 2004;Ghisovan et al, 2008;Duret et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means the excitation is from reference cell to the target cell [79,81]. Figure 5c corresponds to the synchrony between two neurons, as the peak straddles zero [73,82]. This means there is a common excitatory input to both neurons most likely from other neuron or neurons.…”
Section: Crosscorrelograms and Neuronal Relationships In Visual Cortexmentioning
confidence: 99%
“…Adaptation may occur at different timescales (Bao & Engel, 2012; Patterson, Wissig, & Kohn, 2013). Intrinsic synaptic and neuronal mechanisms and extrinsic network interactions may be important for adaptation (Dhruv, Tailby, Sokol, & Lennie, 2011; Ghisovan, Nemri, Shumikhina, & Molotchnikoff, 2008; Sanchez-Vives, Nowak, & McCormick, 2000). …”
Section: Introductionmentioning
confidence: 99%